En højgruppe ved Kvindvad, Vestjylland - Ebbesen, Klaus (Kuml, 2004)
A group of mounds near Kvindvad in Western Jutland The group of mounds in question is situated near Kvindvad in Western Jutland, a little more than ten kilometres from the town of Herning (Figs. 1-3). It is the only known group of mounds from the late Neolithic Age in Denmark. It consists of four mounds situated close together on the western side of a ridge. All the graves are dagger graves, and two of them are tiered graves. In mound no.1 (Figs. 4-6), a rectangular east-west orientated tiered grave was identified. It had been dug 0.6 metres into the subsoil and had a filling of earth and stones. The grave structure was covered by a stone paving. Grave A, which contained a flint dagger of type IA, was dug 0.4 metres into the subsoil. Grave B, also containing a flint dagger of type IA, was found at the bottom of grave A. This grave had faint traces of a wooden coffin. Mound 2 (Figs. 7-8) had been built over just one burial. This grave had a northeast-southwest orientation and was filled with stones. Colouring of the earth showed that the grave had contained a wooden coffin. The grave contained a flint for striking fire, recycled from a flint dagger of type Ix. Mound 3 (Figs. 9-10) had a diameter of 8 to 10 metres and a height of 0.25 to 0.30 metres. It had been constructed above a deep dagger grave with the faint remains of a wooden coffin. The grave was filled in with earth and stones. In the southwestern corner of the grave, a small heap of cremated bones and a pottery sherd were found a little above the bottom of the grave. Mound 4 (Figs. 11-15) had a diameter of 10 metres and a height of 0.25 to 3.0 metres. It had been constructed over a stone paving, which covered a tiered grave. The grave had a northwest-southeast orientation and was filled with stones. At a depth of 0.4 metres were the faint remains of a wooden coffin (grave A). It contained a flint dagger of type IA/B and a slate whetstone pendant. At the bottom of the grave (grave B) was a carefully made stone paving, on top of which yet another coffin had been resting. Two arrowheads with a concave base belong to this grave. The construction of the mounds corresponds to the older mounds known from the single grave culture. All four mounds contained so-called “deep dagger graves,” i.e. graves dug at least 1 metre into the subsoil. Almost all deep dagger graves are found in Northern and Central Jutland, with a marked concentration in Northwestern Jutland. Almost all deep dagger graves date from the late Neolithic Age A, with just a few dating from the late Neolithic Age B. The structures in two of the mounds are so-called tiered graves, which are characterized by having two burials in the same hole, one on top of the other. This is a very special burial custom, which occurs sporadically in the early and the late Neolithic Age across large parts of North and Central Europe. As is the case in the mounds at Kvindvad (Figs. 16-18), flint daggers are in general the most common grave goods in late Neolithic male graves. Slate pendants, on the other hand, occur only sporadically. The arrowheads with a concave base probably represent yet another weapon, i.e. the bow and arrow. These arrowheads are defined by a length not exceeding 8 cm, and by their concave base. This type occurs at the beginning of the late Neolithic Age and continues until period V of the Bronze Age (2400-600BC). So far, no one has succeeded in creating a typological and chronological classification of them. Generally, the arrows have a length of 2 to 6 cm and a thickness of 5 mm. Arrowheads with a concave base often occur in graves (some may even be the cause of death). Their numbers vary from one to twelve (Fig. 21). They occur in at least 57 late Neolithic closed graves. In 31 cases they occur together with flint daggers of type I, in seven cases in combination with daggers of type II. The burial custom of sending the dead to the grave with a bow and arrows thus seems to be primarily from the late Neolithic period A, but it continues into period B. In the later periods, the arrows occur more sporadically as grave goods. Graves containing arrows with a concave base show a clear concentration in Northern Jutland, where they occur mainly in the area surrounding the western Limfjord (Figs. 19-20). Ebbe Lomborg (1973 – cf. 1959 and 1968) divided the country into two geographic zones. Zone I comprised Northern Jutland and the islands, zone II comprised Southern Jutland and Schleswig-Holstein. The boundary between the two areas ran across Central Jutland. The grave types and burial customs described here occur across this boundary and in both zones. Moreover, neither the distribution nor the use of late Neolithic jewellery provides any evidence to support the traditional zone division. The same applies to grave forms and burial customs. The most frequently found burial custom in the late Neolithic Age is the burial of the dead in the old megalith graves. This burial custom is known from all over the country and throughout the age. Stone cists can be divided into at least two different types, which can be separated chronologically and geographically: 1. Small, north-south oriented stone cists (“stenkister” in Danish), which occur only in Northern Jutland during the early part of the late Neolithic Age. They probably originate from the early Neolithic stone cists, and were also built during the late Neolithic Age. 2. The so-called “Zealandic stone cists”, which are known only from Eastern Denmark, with a marked concentration in Northern Zealand. Almost all date from period C of the late Neolithic Age. These stone cists should be regarded as part of a larger context including Western Sweden and other areas of the Scandinavian Peninsula. They are connected to the late Western European megalith tradition, which became widespread in Western Sweden primarily during the end of the late Neolithic Age, but which also involved nearby parts of Denmark. It is noteworthy that these Western European contacts passed directly from Western Europe to Western Sweden – for the most part without passing through Denmark. Late Neolithic burial mounds are almost exclusively a Jutland phenomenon, although primary mound graves are rare. Among these, the deep dagger graves have an important position, as shown above. Among the “secondary” mound graves, the so-called “upper graves” are the most frequent form. In these, the coffin is surrounded by stone packing and is placed in the upper part of an old burial mound, usually an old single grave mound. The type is therefore almost exclusively found in the area where single grave mounds occur. Flat burials occur sporadically all over the country, with a characteristic concentration in Eastern Zealand. Late Neolithic cremation graves occur only randomly in Northern Jutland, and in an early part of the age. As neither the grave types nor the burial customs support Ebbe Lomborg’s zone grouping, this has to be rejected as regards the late Neolithic Age. As regards the early Bronze Age, the division of Denmark into zones has been justified by the fact that Southern Jutland had connections with the Sögel-Wohlde-circle and the western mound grave culture, whereas the rest of the country had direct contacts to Central Europe. The regional differences known from Northern Germany, as recognized from the bronze objects, thus applied in Denmark as well during the Bronze Age. In relation to the period prior to this they must be rejected. During the late Neolithic Age, Denmark consisted of small geographical areas, each with its own characteristics, just as was the case during the early and middle Neolithic Age. By the beginning of the late Neolithic Age, the area surrounding the Limfjord was the most important of these local areas. This is mainly expressed in the pottery, which is decorated in the Myrhøj style. It is possible that important elements of the late Neolithic culture came into existence in the area by the beginning of this age. The late Neolithic Age spans a very long period of time with a very rich and versatile source material. According to the C-14 datings, this age lasted for approximately 700 years, from c.2400 to c.1700 BC. The flint daggers which appear at the beginning of this age dominate. They are used as a stabbing weapon, as a stone for striking fire, and as a knife. The spearheads also represent a new weapon type. Other new items by the beginning of the age are spoon-shaped scrapers, and food knives. Crescent-shaped flint sickles (type I is symmetrical, type II is asymmetrical, i.e. they have their widest point near one of the tips) replace flint flake sickles. An important novelty by the early Neolithic Age is also the vertical loom and a general change in style of dress. By and large, the early Neolithic houses are unknown, and so it is impossible to determine whether the large longhouses from the late Neolithic Age also represent a novelty. The evidence suggests that the changes at the beginning of the late Neolithic Age happened very quickly, probably within a generation. After that, late Neolithic society was marked by conservatism that was extreme, even in the context of Stone Age peasant society. The changes during the nearly 700 year long period are few and insignificant. Denmark in the late Neolithic Age must be characterized as a tribal society. No decisive social differences are recognizable. The basic occupation was farming, primarily animal husbandry. Apart from this, a small late-Neolithic element known from the old kitchen middens from the Ertebølle culture provides indications of some sea hunting and fishing. The very large late-Neolithic houses indicate that all inhabitants of a settlement lived under the same roof. Most likely, power within the society lay in the hands of the old men, which would explain the extreme conservatism. Development was slow and kept within the framework already created during period A of the late Neolithic Age. Bronze Age phenomena from Western and Central Europe were adopted with huge delays and adapted to local traditions. These conditions only changed slowly during C/Per I of the late Neolithic Age. It was not until Bronze Age period II that the old pattern was broken and Danish society developed into a new society ruled by chieftains. Klaus Ebbesen Hørsholm Translated by Annette Lerche Trolle